Pengembangan Sistem Rekomendasi Peminatan untuk Siswa SMA Menggunakan Metode Perekomendasian AHP-SAW (Studi Pada SMAN 6 Malang) - Wendi Kurnia Putra; Yusi Tyroni Mursityo; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Specialization at SMAN 6 Malang still uses manual system that can cause problems for length of time in the specialization process and the possibility of inputting data errors. The system in this study was developed to assist the specialization process at SMAN 6 Malang starting from the collection of specialization questionnaires to producing recommendations for student interest. Specialization recommendations are generated using the AHP method as the priority determinant of the criteria for each interest and the SAW method for calculating and ranking the value of student interest preferences. The system developed by RUP method where in the inception phase produces a to-be business process from as-is. The elaboration phase produces 29 functional requirements and 2 non-functional requirements, as well as the design of use case diagrams, sequence diagrams, class diagrams, physical data models, and system interfaces. Then in the design construction phase is implemented into the programming language, then the system is tested using black box testing which produces valid values for a total of 35 test cases, and compability testing which indicates that the system can run well in most browsers. And the last phase is transition used for deployment. This research produces a website-based system that can assist process of recommendation student interest.